Waikiki A History of Forgetting and Remembering - Chan, Gaye; Feeser, Andrea (University of Hawaii Press, 2006)
Waikiki:A History of Forgetting and Remembering presents a compelling cultural and environmental history of the area, exploring its place not only in the popular imagination, but also through the experiences of those who lived there. Employing a wide range of primary and secondary sources-including historical texts and photographs, government documents, newspaper accounts, posters, advertisements, and personal interviews-an artist and a cultural historian join forces to reveal how rich agricultural sites and sacred places were transformed into one of the world's most famous vacation destinations.The story of Waikiki's conversion from a vital self-sufficient community to a tourist dystopia is one of colonial oppression and unchecked capitalist development, both of which have fundamentally transformed all of Hawai'i. Colonialism and capitalism have not only changed the look and function of the landscape, but also how Native Hawaiians, immigrants, settlers, and visitors interact with one another and with the islands' natural resources. The book's creators counter this narrative of displacement and destruction with stories-less known or forgotten-of resistance and protest